Case Analysis On Cancar Metron (M) Sdn Bhd. - Phaik, Tan Saw (2002)
Cancar Metron (M) Sdn. Bhd. is a factory that manufacturers fastening system. The fastening system are screws which are very small and these screws are used in computers, handphones, televisions, radios, videos and all types of electrical products. There is high labour turnover in almost every department in the factory especially the production department whereby the labour turnover is the highest. The labour turnover rate is at least five people per month in the factory.